First multicentre report of in vitro resistance rates in candidaemia isolates in Turkey. (September 2019) - Arikan-Akdagli, Sevtap; Gülmez, Dolunay; Doğan, Özlem; Çerikçioğlu, Nilgün; Doluca Dereli, Mine; Birinci, Asuman; Yıldıran, Şinasi Taner; Ener, Beyza; Öz, Yasemin; Metin, Dilek Yeşim; Hilmioğlu-Polat, Süleyha; Kalkancı, Ayşe; et al.
Highlights: First multicentre study from Turkey on antifungal resistance in candidaemia isolates. Remarkable fluconazole resistance in C. parapsilosis SC (overall, 7.7%; range, 0–47.1%). Rate of fluconazole resistance in C. glabrata SC was as low as 0.9%. No echinocandin resistance was observed in any of the isolates. Abstract: Objectives: This study investigated the antifungal resistance rates of isolates from candidaemia patients in 12 tertiary-care centres in Turkey. Methods: A total of 1991 Candida spp. isolates from 12 centres isolated from 1997–2017 were included in the study. Species/species complex (SC) identification was performed using conventional methods in all centres, occasionally accompanied by MALDI-TOF/MS. Antifungal susceptibility testing was performed for amphotericin B, fluconazole, itraconazole, posaconazole, voriconazole and micafungin (as echinocandin class representative) using the CLSI microdilution method. Resistance rates were determined according to CLSI clinical breakpoints (CBPs). For drugs and species with undetermined CBPs, epidemiological cut-off values were used for wild-type (WT)/non-WT categorisation. Results: No or low rates of resistance were detected in general for tested Candida spp. isolates. Specifically, overall resistance to fluconazole in isolates of Candida parapsilosis SC and Candida glabrata SC were 7.7% and 0.9%, respectively. Resistance rates for C. parapsilosis SC varied extensively from one center to other (0–47.1%). Importantly, no echinocandin resistance was detected. Rates of non-WT isolates were also generally low: fluconazole against Candida lusitaniae, 4.3%; posaconazole against C. parapsilosis SC, 3.5%; posaconazole against Candida krusei, 1.9%; and voriconazole against C. glabrata SC, 0.5%. Conclusion: This is the first multicentre report of antifungal resistance rates among candidaemia isolates in Turkey, suggesting low resistance rates in general. Due to varying rates of fluconazole resistance in C. parapsilosis SC isolates that was detected at remarkably high levels in some centres, further studies are warranted to explore the source, clonal relatedness and resistance mechanisms of the isolates.